New Films - Refuge Editor (Refuge: Canada's Journal on Refugees, 1983)
Sanctuary: An African Epic focuses on the efforts made by governments and UNHCR to find durable solutions for refugees on that troubled continent. The 28-minute production, shot in 1982 in Somalia, Sudan, Tanzania and Zimbabwe, is narrated by Orson Welles, and was filmed by Dick Young Productions of New York City.